5.0k views
1 vote
Solve for x. 5(x - 3) + 4(x + 3) = 3(x - 1)

2 Answers

3 votes

Answer:

5( x− 3 ) + 4 ( x +3)

9x − 3 = 3(x− 1 ) Simplify 3 ( x − 1 ) .

9 x − 3 = 3 x − 3

Move all terms containing x to the left side of the equation.

6 x − 3 = −3

Move all terms not containing x

to the right side of the equation.

6 x = 0

Divide each term by 6 and simplify.

x = 0

User Olivrg
by
5.6k points
5 votes

Answer:

x = 0

Explanation:

5(x - 3) + 4(x + 3) = 3(x - 1)

5x - 15 + 4x + 12 = 3x - 3

5x + 4x + 12 - 15 = 3x - 3

9x - 3 = 3x - 3

9x = 3x - 3 + 3

9x = 3x

9x - 3x = 3x - 3x

6x = 0

6x ÷ 6 = 0 ÷ 6

x = 0

User Vikram Biwal
by
5.6k points